Static and dynamic brittle fracture - Yaghi, Anas H. (1993)
The project examined the static and dynamic fracture mechanics of brittle materials. Destructive testing was performed on brittle, elastic, isotropic and homogeneous epoxy resin specimens made of Araldite CT-200 with Hardener HT-907.